2015
DOI: 10.3390/ijerph120100829
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Recreational Sports Participation among Taiwanese Adults

Abstract: This study examines the gender differences in the enjoyment of recreational sports participation among Taiwanese adults. Data were obtained using the 2007 Taiwan Social Change Survey. The questionnaire included a topical module of the International Social Survey Program regarding leisure time and sports. Results showed that male subjects were more likely to participate in recreational sports to improve their appearance and on account of their personal interest. In addition to these factors, female subjects als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…However, ranking of motivations for female athletes showed that teamwork, fun and fitness were more important. These results are consistent with previous studies (Egli et al, 2011;Jakobsen & Evjen, 2018;Konderic et al, 2013;Pfeiffer & Pate, 2006;Tsai et al, 2015). Egli et al (2011) concluded that there was a significant difference between the sports participation motivation of male and female athletes, with male athletes' motivation being competition and skill development, while female athletes considered fitness as the most important reason.…”
Section: Discussionsupporting
confidence: 91%
“…However, ranking of motivations for female athletes showed that teamwork, fun and fitness were more important. These results are consistent with previous studies (Egli et al, 2011;Jakobsen & Evjen, 2018;Konderic et al, 2013;Pfeiffer & Pate, 2006;Tsai et al, 2015). Egli et al (2011) concluded that there was a significant difference between the sports participation motivation of male and female athletes, with male athletes' motivation being competition and skill development, while female athletes considered fitness as the most important reason.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that boys had a significantly higher PARI incidence, injury risk and injury rate than girls (42.0% vs. 25.0%, 0.89 vs. 0.46 and 1.52 vs. 1.28) and different potential risk factors were found between genders, which was consistent with previous research [5,17]. Compared with girls, boys tend to be more motivated and active to engage in PA [26,27], which might elevate their exposure to PARI. This was supported by our results (boys: 97.25 min/day; girls: 59.31 min/day).…”
Section: Discussionsupporting
confidence: 89%
“…The younger mean age of women, compared with men, should be mostly due to sociological factors, such as the delayed participation of women in this sport for the first time (1977 in women vs 1975 in men). The lower rates of women participation in 50-km ultramarathon race are in agreement with studies examining sex differences in sports participation and are associated with sex differences in motivation, 16 which may have their origin in childhood, 17 adolescence, 18 and young adulthood. 19 …”
Section: Discussionsupporting
confidence: 87%